Thermoresponsive Polymers for Nuclear Medicine: Which Polymer Is the Best? - Sedláček, Ondřej; Černoch, Peter; Kučka, Jan; Konefal, Rafał; Štěpánek, Petr; Vetrík, Miroslav; Lodge, Timothy P; Hrubý, Martin (Langmuir, 2016)
Thermoresponsive polymers showing cloud point temperatures (CPT) in aqueous solutions are very promising for the construction of various systems in biomedical field. In many of these applications these polymers get in contact with ionizing radiation, e.g., if they are used as carriers for radiopharmaceuticals or during radiation sterilization. Despite this fact, radiosensitivity of these polymers is largely overlooked to date. In this work, we describe the effect of electron beam ionizing radiation on the physicochemical and phase separation properties of selected thermoresponsive polymers with CPT between room and body temperature. Stability of the polymers to radiation (doses 0-20 kGy) in aqueous solutions increased in the order poly(N-vinylcaprolactam) (PVCL, the least stable) ≪ poly[N-(2,2-difluoroethyl)acrylamide] (DFP) < poly(N-isopropylacrylamide) (PNIPAM) ≪ poly(2-isopropyl-2-oxazoline-co-2-n-butyl-2-oxazoline) (POX). Even low doses of β radiation (1 kGy), which are highly relevant to the storage of polymer radiotherapeutics and sterilization of biomedical systems, cause significant increase in molecular weight due to cross-linking (except for POX, where this effect is weak). In the case of PVCL irradiated with low doses, the increase in molecular weight induced an increase in the CPT of the polymer. For PNIPAM and DFP, there is strong chain hydrophilization leading to an increase in CPT. From this perspective, POX is the most suitable polymer for the construction of delivery systems that experience exposure to radiation, while PVCL is the least suitable and PNIPAM and DFP are suitable only for low radiation demands.
Keywords: molekulová hmotnost; Nuclear Medicine; polymery; Acrylic Resins; teplota; akrylové pryskyřice; Polymers; nukleární lékařství; Temperature; Molecular Weight